PORE PRESSURE ANALYSIS OF TKA FIELD BANGGAI BASIN, CENTRAL SULAWESI - Irano, Teddy
TKA field is a hydrocarbon producer structure in the form of oil which located in the Banggai Basin. TRA prospect is 5 km southwest of the TKA field which has the same play. Pore pressure prediction has significant implications to determine the drilling successes and effectiveness. This analysis discusses the pore pressure prediction in Banggai Basin using five wells wireline log data, 110 km2 of 3D interval velocity seismic data and well report of Tiaka Field. Research method using those five wells with The Eaton method for predicting the pore pressure and distribution of its result with 3D interval velocity seismic data. Pore pressure prediction in the well was determined based on effective stress value from check shot interval velocity data, hydrostatic pressure was obtained from hydrostatic gradient and overburden pressure was obtained based on density data. 3D pore pressure modelling was generated from 3D model of effective stress from Normal Compaction Trend (NCT) each well, hydrostatic gradient model using Gardner’s equation from 3D interval velocity model. The results of pore pressure analysis of each well show that overpressure indication was in TKA-1, TKA-2, TKA-4 and TKA-5. Meanwhile, TKA-3 has hydrostatic pressure. Pore pressure prediction of each well and modelling indicate that overpressure occurs within Matindok Formation intervals 6550 – 7583 ft (1996 – 2311 m). The overpressure is caused by two mechanisms, loading mechanism due to rapid sedimentation which not followed by the discharge of water in the rock pores and affect to rock compaction where constant value of effective stress. The tectonic compression activity that occurs in the study area also increases lateral stress which results spreads laterally of overpressure area. On the other hand, the presence of hydrocarbon in the Tomori Formation also causes an overpressure in Matindok Formation. The difference between fluid density and pore water causes the pressure is generated by the buoyancy and induce overpressure zone. In this case the overpressure occurs around the top of the structure. The results of this study can be applied in exploration and development drilling well planning which includes well location, trajectory, well design and the amount of mud weight value of water based mud that will be used during drilling at each interval in the TKA structure. The analogy of modelling pore pressure on the TKA structure is also plan to use in the TRA prospect which similar structure to TKA, the area of overpressure located in around the top of the structure at Matindok Formation.